Sheath fold development around deformable inclusions: Integration of field-analysis (Cima Lunga unit, Central Alps) and 3D numerical models. (March 2021) - Maino, Matteo; Adamuszek, Marta; Schenker, Filippo L.; Seno, Silvio; Dabrowski, Marcin
Abstract: We investigated complex tectonic structures within a km-scale shear zone (Cima Lunga unit), which is traditionally interpreted as generated by multiple, distinct deformation phases, despite showing unique schistosity and lineation. Based on structural analyses we discovered sheath folds developed in relatively weak gneissic/schistose rocks, enveloping inclusions of stronger ultramafics. The internal layering of inclusions experienced superimposed folding, boudinage and folding, attesting to layer-parallel shortening followed by stretching and further again shortening. Using 3D numerical modelling, we explored the structure evolution within and around deformable viscous inclusions under far-field simple shear. The numerical results showed that the internal deformation of ellipsoidal inclusions and the fold development around the inclusions are both dependent on the viscosity ratio, shear strain and the inclusion aspect ratio. The Cima Lunga structural patterns were reproduced for finite strains exceeding 7.5 and viscosity ratio between 2.8 and 9. Inclusions are characterized by persistent rotation of the internal layering, resulting in super-simple shear regime, with kinematic vorticity number >1. An important corollary is that ultramafics and host rocks experienced coupled deformation since the prograde metamorphic evolution. Finally, we emphasise that progressive deformation in shear zones may offer sufficient explanation for complex structural patterns, without invoking unjustified polyphase deformation. Graphical abstract: Image 1 Highlights: We study 3D deformation pattern within and around deformable inclusion in simple shear. Sheath folds can develop around deformable inclusions. Super-simple shear deformation develop within deformable inclusions. Cima Lunga structures are likely formed during single, progressive deformation phase. Backward modelling supplies constraints on the rock rheology and shear strain.